All roads lead to Rome [videorecording (DVD)] - Parker, Sarah Jessica; Day, Rosie; Bova, Raoul, 1971-; Cardinale, Claudia, 1939- (Entertainment One Films Canada, 2016)
Maggie is an uptight, single mother who, in an effort to reconnect with her troubled teen daughter Summer, takes her to the Tuscan village where she used to visit in her youth. There Maggie runs into her former lover Luca and his mother, Carmen. When Summer and Carmen impulsively steal Luca's car and race off to Rome, Maggie and Luca follow in close pursuit.